La representación internacional de Colombia y el Tratado con las Provincias Argentinas, 1825 (Dossier: El momento colombiano de las repúblicas andinas. Desde el concepto de Colombia hasta el reconocimiento internacional) - Kloster, Mariano Ignacio (2021)
The present article examines the treaty between the Republic of Colombia and Buenos Aires signed in 1823 and ratified by the Constitutional Convention of the Argentine Provinces in 1825. Discussions about this action highlight two phenomena inherent to international recognition: on the one hand, the dynamics of nationalizing sovereignty in the Argentine Provinces, and on the other hand, the overlapping offices held by Dean Gregorio Funes, who was both a member of parliament representing the province of Córdoba and Colombia’s trade representative to the Argentine Provinces.